Correlação entre Anemia, Amputação e morte em pacientes com Pé Diabético estratificados pelo Sistema WIfI (Wound, Ischemia, and foot Infection): coorte retrospectivo - Isabela Ferreira Cata Preta (2021)
Objective: To correlate the grades of anemia with the stages of amputation risk of the WIfI classification system (Wound, Ischemia, and foot Infection), and the rates of major amputation, mortality and amputation-free survival in hospitalized patients with diabetic foot. Material and Method: Retrospective cohort study in 443 patients with diabetic foot admitted to a tertiary hospital. Data were collected on clinical, demographic and laboratory information (particularly blood count, C Reactive Protein (CRP), creatinine and hemoglobin A1C) at admission and during the follow-up period, between January 2015 and December 2017. Patients were classified as non-anemic and with mild, moderate and severe anemias. The amputation risk stages were stratified by the WIfI (Wound, Ischemia and foot Infection) classification system into very low, low, moderate and high risk. Statistical analysis used the R Software and the SPSS program for descriptive and comparative statistics. Results: The median age was 65 years and 62% were men, 89% were hypertensive patients (prevailing among women). The median of the lowest hemoglobin level was 9.97 g/dL and of the highest CRP dosage was 59.5mg/L. In the sample, 86.4% had some degree of anemia, almost two thirds (63.4%) with the more advanced grades of anemia, with a prevalence of 76% in women compared to 58% in men (p-value=0.004). According to the WIfI classification, 70% of patients were classified as moderate and high risk of amputation and 89% of those with severe anemia were in the moderate and high risk of amputation. Almost two-thirds (65%) of patients with severe anemia were in the high-risk stage of amputation (stage 4). It was found that the higher the amputation risk stage, the higher the rates of patients with microcytic and hypochromic anemia. Patients in moderate and high amputation risk stages had CRP dosage greater than 10 mg/dL, which was associated with the more advanced grades of anemia. Length of hospital stay was also associated with the grades of anemia (p-value<0.001). During hospitalization, 14.1% of patients with moderate anemia and 47.4% of patients with severe anemia underwent major amputation (p<0.001), increasing respectively the risk of major amputation in 9.81 times and 53 times compared to non-anemic patients (p<0.001). No non-anemic patient underwent major amputation. At admission, moderate anemia decreased amputation-free survival (OR 0.19; 95% CI 0.04-0.83) and severe anemia increased mortality rates (OR 7.53; 95% CI 1.69- 33.52). Overall, severe anemia increased the chances of major amputation by 13.81 times (95% CI 5.09-37.52; p<0.001) and by 3.56 times the chances of mortality (95% CI 1.45- 8.71; p=0.006). In addition, severe anemia was present in 47% of all deaths and led to an 89% reduction in the chances of amputation-free survival (OR 0.11; 95% CI 0.05;0.24). Conclusion: Anemia is an important clinical predictor associated with the severity of the amputation risk stages of the WIfI classification system, increasing amputation and mortality rates, and reducing amputation-free survival. Keywords: Anemia. Diabetes Mellitus. Diabetic foot. Amputation. Mortality.